Cervical and ocular vestibular evoked myogenic potentials in epileptic patients - Abd El Mageed Hassan Kabel; Khaled Hatem Afifi; Samar Mohammed ElFakhrany; Asmaa Salah Moaty (The Egyptian Journal of Otolaryngology, 2021)
Abstract Background Vertigo and dizziness are very common complaints that may be related to epilepsy. The purpose of this study was to assess vestibulo-spinal and linear vestibulo-ocular function in epileptic patients in the inter ictal period. The current observational study was carried out in audio-vestibular unit Menoufia University. Subjects in the current study were divided into two groups: The control group included 30 normal individuals not complaining from any dizzy symptoms and the epileptic cases group included 30 epileptic patients. All subjects in the study were submitted to cervical and ocular vestibular evoked myogenic potential. Results There was no significant difference between the control and epileptic group regarding the age and sex distribution. Sixty-seven percent of epileptic cases had dizzy symptoms. There was statistically significant difference in the latency and amplitude of c and o VEMP between the control and the epileptic group, 39/60 ears (65%) in the study group had cVEMP abnormalities, 32/60 ears (53%) had oVEMP abnormalities. Abnormal c and o VEMP were reported in 28/60 ears (46.7%). There was statistically significant relationship between VEMP abnormalities and duration of seizures, frequency of epileptic attacks, and type of therapy. Conclusion Vestibular abnormalities were frequently reported in epileptic patients in the current study which may be related to the severity and control of epilepsy.